Art Cities, Cultural Districts and Museums - Luciana, Lazzeretti (Firenze University Press, 2004)
The subject of economic valorisation has become a current topic and the idea that culture can be considered a factor of economic production, able to generate wealth, appears to have been generally accepted. The book consists of a series of essays about the economic valorisation of the cultural, artistic and environmental heritage of the art city of Florence using a business economics approach and will appeal to scholars and researchers focusing on the cultural economics and managerial economics of art and to practitioners in the cultural sector and policy makers.